Analisis SWOT Pada Pemasaran Batik Benang Bintik Lestari Indah Palangka Raya - Alexandro, Rinto; Putri, Windy Utami; Nurmawati, Yanti (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
This research uses a qualitative approach with a descriptive method, which is the research in question to gather information about the status of existing symptoms, namely the status of a symptom as it is at the time of research. The research aims to determine the right strengths, weaknesses, opportunities, threats and strategies to apply to Lestari Indah. The results of this research show that the strength owned by Lestari Indah yarn Batik is always maintain quality products and high quality but with an affordable price, Batik motifs and colors are varied and with a sprightly understand the wishes of consumers to the product. The strategic location also becomes the strength of Lestari Indah. The weakness in sustainable freckle yarn Batik is the limited number of employees, the risk of decreasing revenue and high distribution cost rates. Batik Freckles Lestari Indah has the opportunity of increasing community income, the ability to capture market share, the presence of corporate cooperation with consumers, positive response of consumers to the existence of the company. The threat to the beautiful sustainable yarn spots Batik is the large number of competitors and high risk of business. A precise strategy that can be used Lestari Indah is an aggressive growth strategy with market penetration.